THE INFLUENCE OF EQUATORIAL ATMOSPHERIC WAVES ON THE DEVELOPMENT OF DOUBLE VORTEX IN EAST INDIA OCEAN - Jannatunnisa, Luthfiyah
Double Vortex (DV) is a pair of cyclonic vortexes that occur simultaneously and are located in the eastern Indian Ocean. The presence of DV can cause weather disturbances and extreme rainfall in western Indonesia (Sumatra, western Kalimantan, and western Java), with a high frequency of DV in the September- October-November (SON) and December- January-February (DJF). It is still unclear from a climatological perspective what influences the development of the DV event. The data used to investigate the relationship between DV development, which is influenced by equatorial wave activity, is by using zonal, meridional, and relative vorticity wind parameters from The European Center for Medium-Range Weather Forecast (ECMWF) Reanalysis 5-th Generation (ERA5) and parameters Outgoing Longwave Radiation (OLR) from The National Oceanic and Atmospheric Administration (NOAA) Physical Sciences Laboratory (PSL). The study period is 2013-2022 for the SON and DJF seasons. DV identification was by reviewing cyclonic patterns in the study area (15°N-15°S and 80°-100°E) from streamlines with a threshold of 2 m/s and categorizing the DV duration based on the 25th, 50th, and 75th percentile values. Then, to obtain information on equatorial wave activity, a filtering process using the Space-Time Spectral Analysis (STSA) method, which shows the decomposition of OLR data by applying the Fourier transformation twice, often referred to as the WK99 method. Furthermore, using composite analysis and vorticity budget for the study period, it was found that the superposition of equatorial waves, between Equatorial Rossby (ER), Mixed Rossby-gravity (MRG), and Kelvin, both produced negative Outgoing Longwave Radiation (OLR) anomalies (the wet phase of the wave) will result in a longer DV duration (8 days). However, if the superposition of these waves produces a positive OLR anomaly or occurs in the dry phase, then the duration of the resulting DV is medium or occurs around 4-5 days. Meanwhile, for short DV duration (3 days), the value of OLR anomaly is smaller than the two previous duration groups. Then, from the calculation of the vorticity budget, it is found that the convergence term is the dominant term that contributes to the increase in vorticity during the DV.